FAKTOR-FAKTOR YANG MEMPENGARUHI INTEGRITAS LAPORAN KEUANGAN DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI - Ayem, Sri; Sari, Putri Rahma (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to determine the effect of financial distress, leverage, and firm size on the integrity of financial statements with independent commissioners as moderating variables. This study took a sample of 18 transportation & logistics sector companies listed on the IDX from 2019 to 2022, which were determined using the purposive sampling method. The research data were analyzed using multiple linear regression analysis and moderate regression analysis (MRA) with the SPSS version 25 program. The results of this study indicate that financial distress and leverage have a positive effect on the integrity of financial statements, while company size has no effect on the integrity of financial statements. Independent commissioners as a moderating variable can strengthen the positive effect of leverage on the integrity of financial statements but cannot strengthen the positive effect of financial distress and company size on the integrity of financial statements. Keywords: Financial Distress, Leverage, Firm Size, Integrity Of Financial Statements, Independent Commissioners